2002
DOI: 10.1038/nature01134
|View full text |Cite
|
Sign up to set email alerts
|

The origin of geomagnetic jerks

Abstract: Geomagnetic jerks, which in the second half of the twentieth century occurred in 1969 (refs 1, 2), 1978 (refs 3, 4), 1991 (ref. 5) and 1999 (ref. 6), are abrupt changes in the second time-derivative (secular acceleration) of the Earth's magnetic field. Jerks separate periods of almost steady secular acceleration, so that the first time-derivative (secular variation) appears as a series of straight-line segments separated by geomagnetic jerks. The fact that they represent a reorganization of the secular variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(110 citation statements)
references
References 17 publications
4
102
1
3
Order By: Relevance
“…4). This is more or less consistent with the arguments of steady diffusion (Voorhies, 1993;Love, 1999) as well as with the arguments for the primary contribution of the advection to the geomagnetic jerks (Bloxham et al, 2002;Olsen and Mandea, 2008;Wardinski et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…4). This is more or less consistent with the arguments of steady diffusion (Voorhies, 1993;Love, 1999) as well as with the arguments for the primary contribution of the advection to the geomagnetic jerks (Bloxham et al, 2002;Olsen and Mandea, 2008;Wardinski et al, 2008).…”
Section: Discussionsupporting
confidence: 69%
“…Whaler 1986). Bloxham et al (2002) found that a constant flow with TO superimposed provided a good fit to observatory SV; such a model requires just a few parameters. However, this conclusion was not based on an inversion of the observatory data themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the behavior of geomagnetic field has significant potential to yield insight into Earth's geodynamics, such as the influence of core-mantle interactions Bloxham, 2000), changes in outer-core flow and geomagnetic jerks (Bloxham et al, 2002;Dumberry and Finlay, 2007;Mandea et al, 2010;Olsen and Mandea, 2008). Besides the geodynamic significance, connections between the geomagnetic field and global climate have been suggested (Courtillot et al, 2007;Gallet et al, 2005;Kent, 1982), but these claims remain controversial (Bard and Delaygue, 2008).…”
Section: Introductionmentioning
confidence: 99%